O Suicídio no contexto universitário: ampliação do conhecimento e das estratégias de prevenção - Cruz, Paloma (Universidade Federal de São Carlos, 2019)
This graduation conclusion work comes from scientific initiation research that proposed to contribute to the expansion of knowledge and construction of suicide prevention strategies at the Federal University of São Carlos. Qualitative study with a) literature review for contextualization and referential analysis of suicide in young university populations, considering the production, in Portuguese, from 2013 to 2018, in the BVS and PAHO databases; b) action research in the perspective of dynamically studying the process of shared knowledge construction and identifying potential actions or difficulties related to the theme in the community. In 2019, eleven weekly group meetings of two hours each were held with the academic community: administrative technicians, students and college professors; all meetings were recorded through a synthesis-narrative validated by the group of participants. The analysis of the results was systematized by the method of data triangulation, with cross-referencing of empirical data, dialogue with the different authors and analysis of the conjuncture. The bibliographic review resulted in 14 texts, analyzed from the thematic categories: data on suicide among young people, risk and vulnerability; taboos and myths; protective factors; current political context of public health care. The data showed a scarcity of studies and materials aimed at analysis and reflection on suicide prevention aimed at college students. The transition period to university carries a dynamic of transformations and impacts in the personal, social, academic and family spheres, predisposing this population to experience mental health problems in the process of suicidal ideation. Thirteen people participated in the action research, in stages of discussion on the topic, identification of local risks and vulnerabilities, planning and action in the square with the community. The lack of support networks, of living spaces, the hierarchy of power relations, the demands experienced in the academic environment were identified by the group as situations of local vulnerability. Factors of family dynamics and interpersonal relationships, the constant overload of tasks in the student routine, socioeconomic vulnerability and the contingency of institutional budget funds were considered as possible aggravating factors in mental health in this population. Integrative care practices, sports, cultural and social movements were identified as devices that promote socialization and protection of this population. The final action in a square, carried out in the context of this research, provided reception and awareness of the theme through the articulation of different actors and social sectors to make the event viable. The collective process provided the creation of an involved group, expansion of knowledge on the subject and on how to offer shelter to those who suffer, survey of possible strategies, and operationalization of a suicide prevention action with the college community.
Suicide in the university context: expanding knowledge and prevention strategies
Keywords: Suicídio; Integralidade em saúde; Estratégias locais; Saúde Mental; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; CIENCIAS DA SAUDE::SAUDE COLETIVA